2012
DOI: 10.3310/hta16290
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for ocular hypertension: an evidence synthesis and economic evaluation.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 332 publications
(262 reference statements)
1
72
0
Order By: Relevance
“…The EQ-5D 3 Level data were obtained from responses from 640 participants with OHT and glaucoma sampled from a secondary glaucoma service. 42 Similar to the study by Burr et al, 42 who suggested that the degree of visual impairment for mild glaucoma is minimal, it was assumed that the score for those individuals in the 'at risk of glaucoma' state would be the same as the score for those with mild glaucoma. Table 47 shows the utility weights used in the model.…”
Section: Costs Of Treatmentmentioning
confidence: 87%
See 2 more Smart Citations
“…The EQ-5D 3 Level data were obtained from responses from 640 participants with OHT and glaucoma sampled from a secondary glaucoma service. 42 Similar to the study by Burr et al, 42 who suggested that the degree of visual impairment for mild glaucoma is minimal, it was assumed that the score for those individuals in the 'at risk of glaucoma' state would be the same as the score for those with mild glaucoma. Table 47 shows the utility weights used in the model.…”
Section: Costs Of Treatmentmentioning
confidence: 87%
“…When the referral IOP was used in place of the ophthalmologist's IOP the specificity was reduced. Such an impact is unsurprising given the known variability in IOP measurements 42 and the use of an absolute cut-off will lead to a regression to the mean effect when another measurement is taken (in this case by a different observer). Removing the VA component had very little impact on the diagnostic accuracy with a slight reduction in the sensitivity and corresponding increase in specificity.…”
Section: Triage Analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal mode of measurement may be impractical or even unethical. The most reliable way to measure eye pressure (intraocular pressure) is through manometry; 446 however, this requires invasive eye surgery. Subjecting participants to clinically unnecessary surgery for the purpose of a RCT is clearly not ethical without very strong mitigating circumstances, particularly as an alternative, even if less accurate, way of measuring intraocular pressure exists.…”
Section: Choosing a Primary Outcomementioning
confidence: 99%
“…The individual rate of progression varies considerably between patients, and it is impossible to know which patients will progress faster; therefore, intensive follow-up is advised (according to glaucoma management guidelines) until the rate is known [46][47][48][49][50] . To avoid an unacceptable burden on future health resources, it is important to better stratify patients according to their risk profiles.…”
Section: Metabolomics In Glaucomamentioning
confidence: 99%